Empowering Village Cluster as Task Force in The Normalization of Disaster Victims’ Physical Problems - Asep Setiawan; Haris Sofyana; Tarjuman Tarjuman; Parta Suhanda (Humanistic Network for Science and Technology (HNST), 2017)
Natural disaster mitigation frequently focuses on the stage of emergency response, while the impacts of the disaster are often ignored. Community empowerment in the normalization of post-disaster physical problems becomes vital to optimally maintain victims’ health. The research aims to test the effectiveness of training village clusters with the competencies for disaster volunteers in normalizing post-natural disaster physical problems, using the quasi-experimental pre-post-test with control group design. Two natural disaster prone areas were selected from two different provinces, namely West Java and Banten. Sample was taken purposively, resulting in 23 people for each group. The findings show an increase in the dimensions of knowledge and attitudes of the village clusters in the normalization of post-natural disaster physical problems (p value 0.000). For the dimension of skills competency, there was a significant difference between the intervention and control groups at the end of the second month, including the ability to measure body temperature (p 0.000), calculate pulse rate (p 0.000), measure breath rate (p 0.036), measure blood pressure (p 0.000), provide basic life support (p 0.000), give wound care (p 0.000), splint a fracture (p 0.000), and use walking aids (p 0.000). The research recommends the importance of the formation and training of village clusters as a form of village community empowerment in disaster prone areas in the normalization of disaster victims’ physical problems. Keywords: Attitude, Disaster physical problem, Knowledge, Skills, Training, Village cluster